(untitled) (Scientific journal of the Fergana State University, 2024)
The article, on a scientific basis, emphasizes the importance of the national idea and ethnic values in educating young people, instilling in their minds a sense of loyalty to the Motherland. The state policy towards youth, national and universal values are also defined. The importance of ethnological and ethnosocial factors in the formation and development of ethnocultural values of the Uzbek people is also shown. The article also examines the role of national ideology in the development of society, the problems of the genesis of national culture, including the importance of national traditions and values in social development. The modernization of Uzbekistan is based on historical foundations and innovative methods of preserving and developing ethnocultural values.